(untitled) (Sciences & Technology. A, exactes sciences, 2002)
The objective of this paper is to present the behavior of some core samples immersed in a fluid container during a saturation technique. The experimental work was carried out by using two different fluids. The results obtained are similar except for the saturation stages. They are caused by different viscosities and surface tensions.